2021
DOI: 10.3390/jcm10112448
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Negative Thinking and Eating Disorders: A Meta-Analysis of the Role of Worry and Rumination

Abstract: The role of worry and rumination in eating disorders (EDs) is controversial. This meta-analysis of the literature is aimed at clarifying the relationship between repetitive negative thinking (RNT) and EDs. In accordance with the PRISMA criteria, a comprehensive search of the literature was conducted on PubMed and PsycInfo from inception to March 2021. Search terms: “eating disorder/anorexia/bulimia/binge eating disorder” AND “worry/rumination/brooding/repetitive thinking”. A manual search of reference lists wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 100 publications
3
25
0
Order By: Relevance
“…The present review adds to the steady accumulation of evidence highlighting the relationship between maladaptive emotion regulation based on rumination and ED symptomatology (Palmieri et al, 2021;Smith, Mason, & Lavender, 2018). Over the recent years, studies using ecological momentary assessments (EMAs) have reported that rumination and repetitive negative thinking predicts engagement in ED behaviour, including body checking and binge eating (Sala, Brosof, & Levinson, 2019;Smith et al, 2021;Svaldi, Werle, Naumann, Eichler, & Berking, 2019).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The present review adds to the steady accumulation of evidence highlighting the relationship between maladaptive emotion regulation based on rumination and ED symptomatology (Palmieri et al, 2021;Smith, Mason, & Lavender, 2018). Over the recent years, studies using ecological momentary assessments (EMAs) have reported that rumination and repetitive negative thinking predicts engagement in ED behaviour, including body checking and binge eating (Sala, Brosof, & Levinson, 2019;Smith et al, 2021;Svaldi, Werle, Naumann, Eichler, & Berking, 2019).…”
Section: Discussionmentioning
confidence: 91%
“…Over the recent years, several reviews have recommended the use of interventions aimed at reducing rumination and repetitive negative thinking, Metacognitive Therapy (MCT) and Rumination-Focused Cognitive Behavioural Therapy (RFCBT), such as in the treatment of EDs (Palmieri et al, 2021;Prefit et al, 2019;Smith et al, 2018;Trompeter et al, 2021). MCT and RFCBT have been successfully used to treat anxiety and depression among other psychiatric disorders, and there is some evidence suggesting that rumination-focused treatments may help reduce the risk of relapse in depression (Normann, van Emmerik, & Morina, 2014;Spinhoven et al, 2018;Watkins et al, 2011).…”
Section: Linical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present review adds to the steady accumulation of evidence highlighting the relationship between maladaptive emotion regulation based on rumination and ED symptomatology (133,134). Over the recent years, studies using ecological momentary assessments (EMAs) have reported that rumination and repetitive negative thinking predicts engagement in ED behavior, including body checking and binge eating (135)(136)(137).…”
Section: Discussionmentioning
confidence: 92%
“…Specifically, numerous lines of evidence suggest that eating disorder symptoms are linked to the use of maladaptive strategies, such as rumination, catastrophizing, and self-blame, that are characterized by persevering thoughts or self-criticism [ 17 , 18 , 19 , 20 , 21 , 22 ]. For instance, several meta-analyses [ 18 , 19 , 23 ] have elucidated relations between eating disorder symptoms and elevated levels of rumination. In particular, Meule et al [ 18 ] found that individuals with restrictive anorexia nervosa and bulimia nervosa report greater use of dysfunctional cognitive regulatory strategies (i.e., self-blame, rumination, and catastrophizing) than healthy controls.…”
Section: Introductionmentioning
confidence: 99%